Bengali Myths - Blurton, T. Richard (London British Museum Press, 2007)
This series of narratives from the rich tradition of Bengali story-telling will draw from the substantial Bengal collections of the British Museum, which range from the courtly to the popular, and date from the 9th century to the present day. It will demonstrate the connections of history and myth, and will feature works from undivided Bengal - that is West Bengal in the Union of India, and the sovereign state of Bangladesh. The beginning of the book will focus on the powerful goddesses such as Durga, whose Puja is celebrated throughout the world wherever Bengalis are settled. Images of this event and of the goddess appear in paintings, prints and clay sculptures. Also well-known is Kali, after whom the city of Calcutta is probably named. Her legendary paradox of blood-thirst and tenderness is clear from the turbulent oil paintings of the 20th century recluse Sachidananda Sen. Poetry and prose descriptions of her story make lively reading. Other important female deities whose exotic stories fill scroll-paintings and popular prints include the snake goddess Manasa, and the goddesses of learning, Sarasvati, and of wealth, Laxmi. Story-telling scrolls which were used for recitation enable these dramatic stories to be told. Each are different in ambiance, from heroic and the adventurous to exquisitely sensuous and erotic sensibility. Gods and goddesses aren't the whole story. Scrolls used by story-telling are filled with exciting myths that cross the Hindu-Muslim divide. The most important of all the scrolls in the British Museum collection, which tells the story of the Muslim saint, Gazi, illustrates the way in which Muslim pioneers penetrated the delta and settled in the swampy, jungle-filled lands.
Include Map, Color Illustrations and Index.
Keywords: Mythology, Indic -- India--West Bengal -- Bangladesh